Representasi Tambatan Media Sosial Akun Instagram @jrxsid “IDI Kacung WHO” (Analisis Wacana Kritis Norman Fairclough) - Muharam, Muhammad Rizky; Dharta, Firdaus Yuni; Santoso, Made Panji Teguh (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research was compiled by Miuhammad Rizky Muharam, a student of the Communication Studies Program, Faculty of Social and Political Sciences, Singaperbangsa University Karawang with the title